Influence of High Temperatures on Rutting in Asphalt Concrete Pavements - Temirovich, Yuldashev Akmal; Kuziboevich, Narmanov Akbar; Tashbaevich, Mamatkulov Muzaffar (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes various factors affecting roads with asphalt concrete pavement and the state of the asphalt pavement as a result of their influence